α 2-Adrenoceptors: Challenges and Opportunities—Enlightenment from the Kidney - William A. Pettinger; Edwin K. Jackson (Cardiovascular Therapeutics)
It was indeed a Don Quixote-like pursuit of the mechanism of essential hypertension when we serendipitously discovered α2-adrenoceptors (α2-ARs) in skin-lightening experiments in the frog. Now α2-ARs lurk on the horizon involving hypertension causality, renal denervation for hypertension, injury from falling in the elderly and prazosin’s mechanism of action in anxiety states such as posttraumatic stress disorder (PTSD). Our goal here is to focus on this horizon and bring into clear view the role of α2-AR-mediated mechanisms in these seemingly unrelated conditions. Our narrative begins with an explanation of how experiments in isolated perfused kidneys led to the discovery of a sodium-retaining process, a fundamental mechanism of hypertension, mediated by α2-ARs. In this model system and in the setting of furosemide-induced sodium excretion, α2-AR activation inhibited adenylate cyclase, suppressed cAMP formation, and caused sodium retention. Further investigations led to the realization that renal α2-AR expression in hypertensive animals is elevated, thus supporting a key role for kidney α2-ARs in the pathophysiology of essential hypertension. Subsequent studies clarified the molecular pathways by which α2-ARs activate prohypertensive biochemical systems. While investigating the role of α1-adrenoceptors (α1-ARs) versus α2-ARs in renal sympathetic neurotransmission, we noted an astonishing result: in the kidney α1-ARs suppress the postjunctional expression of α2-ARs. Here, we describe how this finding relates to a broader understanding of the role of α2-ARs in diverse disease states. Because of the capacity for qualitative and quantitative monitoring of α2-AR-induced regulatory mechanisms in the kidney, we looked to the kidney and found enlightenment.